Multidrug-resistant Shigella flexneri outbreak affecting humans and non-human primates in New Mexico, USA - Sarah Shrum Davis; Paris Salazar-Hamm; Karen Edge; Tim Hanosh; Jessica Houston; Anastacia Griego-Fisher; Francelli Lugo; Nicholas Wenzel; D’Eldra Malone; Carol Bradford; Kelly Plymesser; Michael Baker; et al. (Nature Communications)
Abstract Shigellosis is a gastrointestinal infection caused by species of Shigella. A large outbreak of Shigella flexneri serotype 2a occurred in Albuquerque, New Mexico between May 2021 and November 2023 that involved humans and non-human primates (NHP) from a local zoo. We analyzed the genomes of 202 New Mexican isolates as well as 15 closely related isolates from other states, and four from NHP. The outbreak was initially detected within men who have sex with men but then predominantly affected people experiencing homelessness. Nearly 70% of cases were hospitalized and there was one human death. The outbreak extended into Albuquerque’s BioPark Zoo, causing high morbidity and six deaths in NHPs. All isolates were multidrug-resistant, including towards fluoroquinolones, a first line treatment option which led to treatment failures in human and NHP populations. We show the circulation of the same S. flexneri strain in humans and NHPs, causing fatalities in both populations. This study demonstrates the threat of antimicrobial resistant organisms to vulnerable human and NHP populations and emphasizes the value of genomic surveillance within a One Health framework.